Bovine CD4(+) T-Lymphocyte Clones Specific for Rhoptry-Associated Protein 1 of Babesia bigemina Stimulate Enhanced Immunoglobulin G1 (IgG1) and IgG2 Synthesis - Brown, Wendy C. (American Society for Microbiology, 1999)
Optimal protective immunity against babesial infection is postulated to require both complement-fixing and opsonizing antibodies in addition to gamma interferon (IFN-γ)-mediated macrophage activation. The rhoptry-associated protein 1 (RAP-1) of Babesia bigemina induces partial protective immunity and is a candidate vaccine antigen. Previous studies demonstrated that cattle immunized with native protein that were subsequently protected against challenge had a strong IFN-γ and weaker interleukin-4 (IL-4) response in immune lymph node lymphocytes that reflected the cytokine profile of the majority of CD4(+) T-cell clones obtained from peripheral blood. RAP-1-specific T helper (Th) cell clones that coexpress IFN-γ and IL-4 are typical of numerous parasite-specific clones examined. However, the function of such cells as helper cells to enhance immunoglobulin secretion by bovine B cells has not been reported. In cattle, both immunoglobulin G1 (IgG1) and IgG2 can fix complement, but IgG2 is the superior opsonizing subclass. Therefore, studies were undertaken to ascertain the functional relevance of RAP-1-specific, CD4(+) Th0 cells as helper cells to enhance IgG1 and/or IgG2 production by autologous B lymphocytes. For comparison, Th0 clones specific for the metazoan parasite Fasciola hepatica that expressed relatively more IL-4 than the B. bigemina-specific Th cells were similarly assayed. B. bigemina RAP-1-specific clones could enhance production of both IgG1 and IgG2 by autologous B cells, whereas Th cell clones specific for F. hepatica enhanced predominantly IgG1 production. The capacity to enhance IgG2 production was associated with production of IFN-γ by Th cells cocultured with B cells, antigen, and IL-2. The in vitro helper T-cell activity of these T-cell clones was representative of the in vivo serologic responses, which were composed of a mixed IgG1-IgG2 response in B. bigemina RAP-1 immune cattle and a biased IgG1 response in F. hepatica-immune cattle.